Postpositivism: Extending the Field of Scientific Rationality - Nikolaevna Shadrina, Elena; Vladimirovna Ledeneva, Elena; Albertovna Terekhova, Vera; Agayevich Kuliev, Zakir; Alekseevna Gvozdeva, Galina (Opción, 2019)
Problematization of development of scientific knowledge was the turning point in the positivist philosophy and has led to the formation of a relatively independent area of philosophical studies connected with the development of postpositivist scientific concepts. Nowadays hardly anyone is content with the idea of absolute knowledge, forever remaining in the once achieved state of rest. Understanding the dynamics of knowledge can influence the interpretation of the nature of science. Leading representatives of postpositi- vism, including Karl Popper, Imre Lakatos, Thomas Kuhn, and Paul Feyera- bend focused on the topic of development in science. Different priorities of their studies (from a focus on various practices of scientific research to com- prehensive analysis of social and historical determinants of scientific cogni- tion) did not undermine the common conclusion that purely methodological description of scientific activity is inadequate, and thus, the need to support it with sociological, psychological and culturological descriptions is recog- nized. The usage of comparativistics methods to describe a number of the main postpositivist scientific concepts also allows researchers to identify an additional criterion for their definition and differentiation. If we rely upon the interpretation of rationality as compliance with certain fixed rules and principles, then the model of science developed by Popper and Lakatos will be considered rational as opposed to other views, such as Feyerabend’s theory, every detail of which contradicts this requirement. However, a more extended interpretation of scientific rationality as “reasonability” allows evaluating not only Popper’s theory but also Kuhn’s and even Feyerabend’s models as rational, i.e. pursuing a particular goal. Therefore, the criterion for definition and differentiation of scientific concepts from the perspective of their subjective centrality is effective.